How nestlings of Oriental Reed Warbler respond to adult alarm calls - Jiaojiao Wang; Yongrui Feng; Laikun Ma; Longwu Wang; Canchao Yang; Jianhua Hou (Avian Research)
Avian alarm calls mediate defenses against brood parasites and predators. These calls facilitate communication among adults and alert nestlings to potential danger. While heterospecific call recognition has been extensively studied in adult birds, nestlings—lacking direct predation experience and heterospecific alarm exposure—represent an ideal system to investigate the response to interspecific warning cues. This study explored the recognition capabilities of 5–6-day-old nestlings in Oriental Reed Warbler (Acrocephalus orientalis), a common host of the Common Cuckoo (Cuculus canorus). We exposed the nestlings to playbacks of alarm calls directed at parasites and raptors from conspecific, Vinous-throated Parrotbill (Sinosuthora webbiana, sympatric species), Isabelline Shrike (Lanius isabellinus, allopatric species) and Common Tailorbird (Orthotomus sutorius, allopatric species) adults. Results indicated that there was no significant difference in the responses of nestlings to the alarm calls of conspecific and allopatric adults directed at cuckoos and sparrowhawks. In addition, interestingly, nestlings significantly reduced their begging in response to conspecific and unfamiliar allopatric Isabelline Shrike and Common Tailorbird alarm calls but exhibited a weak response to the sympatric Vinous-throated Parrotbill. Whether older warbler nestlings with more social experience exhibit stronger responses to the alarm calls of Vinous-throated Parrotbill adults requires further investigation.